2020
DOI: 10.1038/s41586-020-2263-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of type 2 diabetes loci in 433,540 East Asian individuals

Abstract: SUMMARY Meta-analyses of genome-wide association studies (GWAS) have identified >240 loci associated with type 2 diabetes (T2D) 1 , 2 , however most loci have been identified in analyses of European-ancestry individuals. To examine T2D risk in East Asian individuals, we meta-analyzed GWAS data in 77,418 cases and 356,122 controls. In the main analysis, we identified 301 distinct association signals at 183 loci, and across T2D association models w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
269
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 336 publications
(305 citation statements)
references
References 83 publications
8
269
2
Order By: Relevance
“…The DIAMANTE (DIAbetes Meta-ANalysis of Trans-Ethnic association studies) Consortium was established to assemble T2D GWAS across diverse populations and develop methodological blueprints for intra-and inter-ancestry meta-analyses relevant to any complex trait. Analyses of the European and East Asian ancestry-specific components of DIAMANTE have previously been reported (4,6). Here, we describe the results of our transancestry meta-analysis of T2D GWAS, which partially overlaps with these ancestry-specific efforts, focussing on genetic variation shared across population groups at loci robustly associated with the disease.…”
Section: Main Textmentioning
confidence: 92%
See 1 more Smart Citation
“…The DIAMANTE (DIAbetes Meta-ANalysis of Trans-Ethnic association studies) Consortium was established to assemble T2D GWAS across diverse populations and develop methodological blueprints for intra-and inter-ancestry meta-analyses relevant to any complex trait. Analyses of the European and East Asian ancestry-specific components of DIAMANTE have previously been reported (4,6). Here, we describe the results of our transancestry meta-analysis of T2D GWAS, which partially overlaps with these ancestry-specific efforts, focussing on genetic variation shared across population groups at loci robustly associated with the disease.…”
Section: Main Textmentioning
confidence: 92%
“…Genome-wide association studies (GWAS) have been extremely successful in identifying T2D susceptibility loci but have mostly focused on populations of European ancestry (1)(2)(3)(4). To address this population bias, more recent largescale T2D GWAS have expanded into East Asian ancestry populations (5,6) and multiancestry biobanks (7,8). The DIAMANTE (DIAbetes Meta-ANalysis of Trans-Ethnic association studies) Consortium was established to assemble T2D GWAS across diverse populations and develop methodological blueprints for intra-and inter-ancestry meta-analyses relevant to any complex trait.…”
Section: Main Textmentioning
confidence: 99%
“… - Nkx6.1 suppresses Gcg expression by targeting PAX6 [ 52 ]. - ARX and GCG genes are completely absent in hiPSC-derived β cells that express NKX6.1 [ 76 ]. Role in β cell proliferation - Nkx6.1 controls the expression of Nr4a1, Nr4a3, and c-Fos, which are crucial for β cell proliferation [ 59 , 60 ].…”
Section: Upstream and Downstream Targets Of Nkx61 Associated With βmentioning
confidence: 99%
“…Mounting evidence suggests that NKX6.1, the β cell-enriched TF, may have a prominent role in the development of T2D. Three genome-wide association studies (GWAS) reports have identified NKX6.1 variants that are associated with T2D in East Asian individuals [ 76 , 78 , 79 ]. Also, decreased expression of NKX6.1 has been shown to be involved in the development of T2D in humans and rodents [ 47 , 80 ].…”
Section: Nkx61 and Diabetes Mellitusmentioning
confidence: 99%
“…Today's, more than 500 million type-2 diabetic patients living in all around the world and this prevalence steadily increasing (1). Painful diabetic neuropathy (PDN) with 60% prevalence is the main complication of diabetic patients, speci ed by feet cramps, burning, numbness and tingling.…”
Section: Introductionmentioning
confidence: 99%